Predicting and Changing Behavior: The Reasoned Action Approach - Fishbein, Martin; Ajzen, Icek (Psychology Press, 2010)
This book describes the reasoned action approach, an integrative framework for the prediction and change of human social behavior. It provides an up-to-date review of relevant research, discusses critical issues related to the reasoned action framework, and provides methodological and conceptual tools for the prediction and explanation of social behavior and for designing behavior change interventions.